Model of organizational and methodological framework of health-enhancing and recreational activities for preschool children in a football club environment - R. Sukhomlynov; O. Andrieieva (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The article addresses the urgent problem of improving the organizational and methodological framework of health-enhancing and recreational activities for older preschool children in children's football clubs aiming at strengthening the health of this population and increasing their involvement in regular physical activity. Objective. To substantiate the model of organizational and methodological framework of health-enhancing and recreational activities for preschool children in a football club environment. Research methods. The following methods were used in the study: theoretical analysis of special scientific and methodological literature and documentary materials, pedagogical and sociological methods, modelling, and methods of mathematical statistics. Results. The model of organizational and methodological framework for health-enhancing and recreational activities of older preschool children in a children's football club environment was theoretically substantiated and developed. The model included organizational, diagnostic, methodological, and control units, as well as the technological and methodological conditions for its implementation to improve safety and the effectiveness of classes for preschool children. The program of health-enhancing and recreational activities involving football skills training, which was a component of the developed model, was substantiated, developed, and implemented. Information and educational components of the model were also developed to increase the level of awareness of parents on health issues. Special training was conducted for children's coaches to increase the level of knowledge on the safety of classes and on the use of health-enhancing and recreational physical activity during classes for older preschoolers. Conclusion. The study has identified the ways to modernization of organizational and methodological framework of health-enhancing and recreational activities for older preschoolers in a football club environment.